2014
DOI: 10.1103/physreve.89.061002
|View full text |Cite
|
Sign up to set email alerts
|

Response function of turbulence computed via fluctuation-response relation of a Langevin system with vanishing noise

Abstract: For a shell model of the fully developed turbulence and the incompressible Navier-Stokes equations in the Fourier space, when a Gaussian white noise is artificially added to the equation of each mode, an expression of the mean linear response function in terms of the velocity correlation functions is derived by applying the method developed for nonequilibrium Langevin systems [Harada and Sasa, Phys. Rev. Lett. 95, 130602 (2005)]. We verify numerically for the shell-model case that the derived expression of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 35 publications
(43 reference statements)
3
13
0
Order By: Relevance
“…By increasing the number of samples, the deviations becomes smaller, however. The worse agreement of H (T) has been anticipated from our previous study of the shell model (Matsumoto et al 2014) since the summations in the shell-model equivalent of (2.15) caused loss of significant digits, in particular, in the inertial range. This is also the case for the Navier-Stokes case, as we will now show.…”
Section: Frr With Random Forcingmentioning
confidence: 77%
See 4 more Smart Citations
“…By increasing the number of samples, the deviations becomes smaller, however. The worse agreement of H (T) has been anticipated from our previous study of the shell model (Matsumoto et al 2014) since the summations in the shell-model equivalent of (2.15) caused loss of significant digits, in particular, in the inertial range. This is also the case for the Navier-Stokes case, as we will now show.…”
Section: Frr With Random Forcingmentioning
confidence: 77%
“…In particular, the twofold cancellations of the Harada-Sasa FRR indicated that the deviation from the FDT is caused by both the nonlinearity and the dissipation. Whether or not the effect of the dissipation diminishes as we increase the Reynolds number, as suggested by the shell-model study (Matsumoto et al 2014), remains to be seen. If the nonlinear part of the Harada-Sasa FRR, which corresponds to the energy transfer function at equal times, becomes dominant at high Reynolds numbers, it is tempting to connect the breakdown of the FDT with the energy cascade.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations